Development and evaluation of the gender-specific CONSTANCES job exposure matrix for physical risk factors in France - Francesca Wuytack; Bradley A Evanoff; Ann Marie Dale; Fabien Gilbert; Marc Fadel; Annette Leclerc; Alexis Descatha (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVES: This study aimed to construct and evaluate a gender-specific job exposure matrix (JEM) for 27 physical work exposures, based on self-report.METHODS: We constructed a JEM using questionnaire data on current physical exposures from 29 381 male and 35 900 female asymptomatic workers aged 18-69 years in the French CONSTANCES cohort study. We excluded workers with musculoskeletal pain to reduce potential reporting bias. We grouped 27 self-reported physical exposures using the French national job codes and stratified by gender. We compared individual and group-based exposures using the performance indicators Cohen's kappa (κ), sensitivity, specificity, and area under the receiver operating curve (AUC).RESULTS: JEM validation showed fair-to-moderate agreement (κ 0.21-0.60) for most physical exposures for both genders except for 'reach behind' (poor), 'bend neck' (poor), 'finger pinch' (poor), standing' (good), 'use computer screen' (good), and 'use keyboard or scanner' (good). We found the highest AUC for 'standing' (men 0.85/ women 0.87), 'kneel/squat' (men 0.80/women 0.81), 'use computer screen' (men/women 0.81), and 'use keyboard or scanner' (men 0.82/ women 0.84). The AUC was <0.60 for only three exposures: 'bend neck' (men 0.58/women 0.57), 'finger pinch' (men 0.56/ women 0.55), and 'reach behind' (men 0.54/ women 0.51).CONCLUSION: The constructed JEM validation measures were comparable for men and women for all exposures. Further research will examine the predictive ability of this gender-specific JEM for musculoskeletal disorders and the relevance of gender-stratification in this process, knowing accuracy of each exposure.